1997
DOI: 10.1038/sj.leu.2400699
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human myeloid leukemia cells induced by an inhibitor of protein phosphatases (okadaic acid) is prevented by Bcl-2 and Bcl-XL

Abstract: 2. 13 On the other hand, Haldar et al 14 described that treatment this report, we found that OA induced apoptosis in three Keywords: Bcl-2; Bcl-XL; apoptosis; okadaic acid; myeloid myeloid leukemia cell lines, which was accompanied by down-regulation of Bcl-2, Bcl-X L and Bax. Furthermore, we also demonstrated that overexpression of either Bcl-X L or BclIntroduction 2 blocked OA-induced apoptosis in K562 cells.Phosphorylation and dephosphorylation of cellular proteins are implicated in many biologically import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 4 publications
4
23
0
Order By: Relevance
“…Furthermore, the prevention of Bcl-2 decrease has been associated with the protective effects of olanzapine on methamphetamine-induced neurotoxicity (He et al, 2004). Thus our own previous data, together with the findings by other investigators that OA-induced apoptosis is associated with downregulation of Bcl-2 and can be prevented by upregulation of Bcl-2 (Benito et al, 1997;Nuydens et al, 2000;Cabado et al, 2004), suggest that Bcl-2 plays an important role in the neuroprotective effects of olanzapine on OA-induced neurodegeneration and apoptosis. Olanzapine may also attenuate OA-induced neurotoxicity by upregulating superoxide dismutase (Manna et al, 1998;Li et al, 1999;Matias et al, 1999), and perform protective effects on OA-induced apoptotic cell death by modulating the expression of pro-and antiapoptotic proteins such as Bax and Bcl-X L (Wei et al, 2003b;Cabado et al, 2004).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the prevention of Bcl-2 decrease has been associated with the protective effects of olanzapine on methamphetamine-induced neurotoxicity (He et al, 2004). Thus our own previous data, together with the findings by other investigators that OA-induced apoptosis is associated with downregulation of Bcl-2 and can be prevented by upregulation of Bcl-2 (Benito et al, 1997;Nuydens et al, 2000;Cabado et al, 2004), suggest that Bcl-2 plays an important role in the neuroprotective effects of olanzapine on OA-induced neurodegeneration and apoptosis. Olanzapine may also attenuate OA-induced neurotoxicity by upregulating superoxide dismutase (Manna et al, 1998;Li et al, 1999;Matias et al, 1999), and perform protective effects on OA-induced apoptotic cell death by modulating the expression of pro-and antiapoptotic proteins such as Bax and Bcl-X L (Wei et al, 2003b;Cabado et al, 2004).…”
Section: Discussionmentioning
confidence: 53%
“…Transfection with 800 nM siRNA duplexes for bcl -2 gene induced a minimal apoptotic response in HL -60, U937, and THP -1 cell lines, which expressed high Bcl -2 levels, but not in the K562 cell line, which is Bcl -2-negative. 31,32 However, a significant induction of programmed cell death (P < .05) was observed after the combined transfection with 400 nM siRNA duplexes for c -raf and 400 nM siRNA duplexes for bcl -2 gene in HL -60, U937, and THP -1 cell lines.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, it was shown that the K562 cell line does not express Bcl -2, but instead expresses high levels of the antiapoptotic protein Bcl -xL from the same family of apoptosis inhibitors. 31,32 It is also possible that the Mcl -1 protein -belonging to the same Bcl -2 family of programmed cell death inhibitors and localized predominantly in the endoplasmic reticulum and nuclear envelope -having a cellular pattern of expression that overlaps with, but is not identical to, that of Bcl -2, 38 plays a significant role in the case of K562 line cells. Indeed, Mcl -1 was found to exert a function analogous to Bcl -2, targeting Raf -1 to mitochondria and reducing cell damageinduced release of mitochondrial cytochrome c -the increase in Mcl -1 proteins correlating with a reduced extent of apoptotic cell death induced by etoposide 39 and by fludarabine.…”
Section: Discussionmentioning
confidence: 99%
“…As described in other models, this effect is likely due to c-Mycinduced apoptosis, as it was partly relieved by using high serum concentrations (not shown) and by enforced expression of Bcl2 (see below). To allow the study of Myc and Ras functional interaction by clonogenic assays, we first generated a K562/S subline with constitutive expression of Bcl-2 (not shown), as K562 cells do not express this antiapoptotic protein (67). We co-transfected K562/S-Bcl2 cells with Ras-G12V-T35S and c-Myc expression vectors in a ratio of 5:1 (Ras/Myc) and scored colonies after selection with hygromycin B, the resistance gene harbored in the c-Myc vector.…”
Section: Miz1 Is Not Required For C-myc Antagonistic Effects On Ras-mmentioning
confidence: 99%